Let sleeping dogs lie - Ledbetter, Suzann (Don Mills, Ont. : MIRA, 2009)
"Private investigator Jack McPhee has a two-word business philosophy: no partners. Rules are allegedly made to be broken, but Jack didn't expect that a contract to nab the so-called Calendar Burglar would force him to team up with a ten-pound, hyperactive Maltese. Or that as McPhee Investigations goes to the dogs, he'd fall deeply in-like with Dina Wexler, an undertall groomer, whose definition of a P.I. comes from watching w-a-a-y too many detective shows. Or that his absolutely genius idea to catch a thief would make him the prime--and only--suspect in a cold- blooded, diabolical homicide."--p. [4] of cover.
Keywords: Private investigators -- Fiction; Theft -- Fiction; Murder -- Investigation -- Fiction; Mystery fiction